The development of viticulture through the prism of the green economy requirement - Alexandrov Eugeniu; Botnari Vasile; Gaina Boris (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The primary imperative of the sustainable development of the wine sector is to obtain high production, with low consumption of resources, in conditions of increased economic efficiency and the use of technological links that contribute to reducing energy consumption. High quality wine derivatives can be provided, taking into account three main factors: genotype (variety), location of the plantation (soil and climatic conditions) and applied technology (cultivation and processing). Intraspecific genotypes have a wide capacity for use, but at the same time do not ensure overcoming the barrier of climate change. That is why, taking into account the functionality of genotypes and the use of technical algorithms and interspecific hybridization methods, more plastic rhizogenic interspecific genotypes should be created in terms of their adaptation to climate change, with beneficial repercussions on the sustainable development of the wine sector. As a result of the crossover of V.vinifera L. with M.rotundifolia Michx. interspecific vine genotypes have been obtained and identified that allow the expansion in the northern area of the vine cultivation area on its own roots, while reducing the number of chemical treatments, which will contribute to obtaining products ecological and environmental protection. Rhizogenic interspecific genotypes possess an early period of grape maturation can be multiplied by pruning, without grafting, thus obtaining rhizogenic propagating material that contributes to reducing the costs of setting up vineyards. They were approved as table grape varieties: "Malena", "Nistreana" and "Algumax" and grape varieties for fresh consumption and processing: "Augustina", "Alexandrina" and "Amethyst". By creating plantations, it will contribute to the extension of the area to the northern limit of vine cultivation.
Keywords: Q01; Q57; 330; area; genotype; green economy; viticulture